Struktur dan Pewarisan Mantra Pasisik di Kenagarian Canduang Kecamatan Ampek Angkek Kabupaten Agam - Rahmah Rahmah; Abdurahman Abdurahman; Bakhtaruddin Nst. (Universitas Negeri Padang, 2013)
The purpose of this study is to describe and analyze the structure of the text mantra, the requirements in the process of inheritance mantra, incantations and supporting aspects Pasisik in Kenagarian Canduang. This research is descriptive qualitative research method. The research findings are from structure aspect using basmallah as the opening mantra, the contents of the mantra is a request to God for temp people into his compassion and love to those who wanted it, and say lailahaillallah as the closing mantra. Supporting aspects of the mantra is: (1) the time of incantations at night, (2) the place of incantations is at home or in requester shaman mantra’s house, (3) an event or occasion of mantra is when there is a request, (4 ) the actors in the chant is someone who is a healer, (5) equipment in the mirror spell, gelundi three branches, rendang peanuts, candy, salt, (6) the dress that usually used is clean regular clothes and close the genitals, (7) the way in bringing the mantra that is sitting cross-legged, concentrating and need a quiet atmosphere. Aspects spell inheritance is bequeathed by the family and learn to implement the conditions studied, the introduction of yourself.